HUBUNGAN METODE MENYIKAT GIGI DENGAN INDEKS PHPM PADA ANAK TUNARUNGU - Sulistyani, Fitria Dwi; Ayun, Quroti; Hidayati, Siti (Poltekkes Kemenkes Yogyakarta, 2021)
The method of brushing teeth is the recommended general method to clean soft deposit on the surface of the teeth and gums. Plaque is transparent thin layer that attached on the teeth. Deaf is a term used for children who experience limitations in hearing. Based on the preliminary study, deaf children in Special needs children school (SLB) in Yogyakarta Special Regionshowed that 80% of the 20 children had moderate PHPM index scores. This research aimed to determine the relationship between the method of brushing teeth and the PHPM index in deaf children. This research used quasy experiment with one group pretest posttest. Moreover, total sampling was used as a sampling technique to collect the data from 50 respondents. Data collection technique was carried out by measuring PHPM index by using disclosing solution before and after the tooth brushing treatment with vertical, horizontal, and mix method. This research was conducted between February and March 2019. Chi-square was used as the statistic test. This study shows that most children used the horizontal tooth brushing method (48%) with p=0,002, mix tooth brushing method with p=0,006, and vertical tooth brushing method with p=0,054. Therefore, it shows that horizontal and mix method have significant relationship with PHPM index (p<0,05). There is a significant relationship between the method of brushing teeth and the PHPM index in deaf children.